OBTURATOR PROSTHESIS TO REHABILIT PALATE AND KENNEDY CLAS III PATIENT - Rahmat Hidayat (Odonto : Dental Journal, 2017)
Background: Cleft palate leads to oroantral communication and also malformations of the palate and agenese of teeth adjacent to the defect. Abnormal defect closure was done by replacing the hard, soft tissues and missing teeth using an intraoral maxillofacial prosthesis called obturator. Purpose: Assess the use of prosthetic rehabilitation using frame obturator combination with acrylic resin on patient’s palatum defect to restore esthetic, speech, swallowing, mastication functions.Case: 23 years old male patient with chief complaint palatum defect that cause nasal voice. Intraoral examination revealed a large palate defect in the right of palatum durum segment, also defect on left labial gingiva, and missing teeth in 13, 15, 16, 21, 22, 23, 24, 25, 26, 35, 36, 45, 46.Case Management: Obturator was made to cover defect of palate and replace missing teeth. Impression was taken with hydrocoloid irreversible and gauze that cover the defect to avoid alginate entering nasal cavity. Insertion of obturator showed cleft palate was covered well by frame combination with acrylic resin base. The retention, stabilization and occlusion were good, nasal voice was reduced, defect on left labial gingiva were covered by labial wing.Discussion: Patient was satisfed because nasal voice was reduced, estethic,mastication and swallowing function were restored, also. Patient can clean and use obturator easily.Conclusion: Frame obturator in patient’s palate defect can reduce nasal voice, restore esthetic, swallowing and mastication functions.